2015
DOI: 10.2174/1567205012666141218125042
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of the β-Secretase Inhibitor GRL-8234 in 5XFAD Alzheimer’s Transgenic Mice Lessen During Disease Progression

Abstract: The β-secretase enzyme BACE1, which initiates the cleavage of amyloid precursor protein (APP) into the amyloid-β (Aβ) peptide, is a prime therapeutic target for Alzheimer’s disease (AD). However, recent investigations using genetic animal models raise concern that therapeutic BACE1 inhibition may encounter the dramatic reduction of efficacy in ameliorating AD-like pathology and memory deficits during disease progression. Here, we compared the effects of the potent and selective small-molecule BACE1 inhibitor G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 57 publications
(86 reference statements)
6
28
1
Order By: Relevance
“…Ts65Dn mice are characterized by a number of phenotypes including progressive loss of working memory, cholinergic deficit in the basal forebrain, neuroinflammation, and endosomal and brain amyloid precursor protein abnormalities, all of which have been observed in AD and mouse models of AD (Hartley et al, 2015). The current findings of impairments in nesting behavior, spontaneous alternation and reversal learning are also consistent with findings in mouse models of AD (Filali and Lalonde, 2009; Morales-Corraliza et al, 2013; Torres-Lista and Gimenez-Llort, 2013; Webster et al, 2014; Devi et al, 2015). Moreover, inflexibility of learning is an early feature of AD dementia (Albert, 1996; Traykov et al, 2007), further linking Ts65Dn as a mouse model of AD.…”
Section: Discussionsupporting
confidence: 89%
“…Ts65Dn mice are characterized by a number of phenotypes including progressive loss of working memory, cholinergic deficit in the basal forebrain, neuroinflammation, and endosomal and brain amyloid precursor protein abnormalities, all of which have been observed in AD and mouse models of AD (Hartley et al, 2015). The current findings of impairments in nesting behavior, spontaneous alternation and reversal learning are also consistent with findings in mouse models of AD (Filali and Lalonde, 2009; Morales-Corraliza et al, 2013; Torres-Lista and Gimenez-Llort, 2013; Webster et al, 2014; Devi et al, 2015). Moreover, inflexibility of learning is an early feature of AD dementia (Albert, 1996; Traykov et al, 2007), further linking Ts65Dn as a mouse model of AD.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, BACE1 may be in excess over APP in 5XFAD males with lower transgenic APP overexpression (~160%) so that 50% BACE1 reduction has little effect on lowering Aβ. In this study, we found no difference in APP expression levels between male and female 5XFAD mice, and APP overexpression relative to wild-type control levels in the 5XFAD model (Tg6799 line) was much higher (300–500%) in a series of previous investigations including ours (Oakley et al, 2006, Ohno et al, 2007, Hong et al, 2013, Devi and Ohno, 2014, Py et al, 2014, Devi et al, 2015). The results using well-established anti-APP antibodies against the C-terminus (C1/6.1) and N-terminus (22C11) are consistent in these studies.…”
Section: Discussioncontrasting
confidence: 48%
“…We hypothesize that the C83 reduction found in BACE1 +/− ·5XFAD mice may reflect a secondary change that occurs as a consequence of prior C99 reduction. This view is supported by our recent pharmacological data demonstrating that administration of the β-secretase inhibitor GRL-8234 to 5XFAD mice induced C83 lowering concomitant with C99 reductions (Devi et al, 2015). The results are also consistent with clinical observations that the C-terminally truncated short fragments of Aβ, which are released by sequential β- and α-cleavage of APP, are elevated in AD compared to non-demented controls and their concentrations change in accordance with the availability of the substrate C99 (e.g., increase by γ-secretase inhibition) (Portelius et al, 2006, Portelius et al, 2010, Portelius et al, 2011).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The brain-penetrable BACE1 inhibitor GRL-8234 showed a rapid decrease in soluble Aβ in the brain of Tg-2576 mice, and long-term treatment up to 7.5 months rescued cognitive defects induced by Aβ in this mouse model (Chang et al, 2011). Once-daily injection of an improved BACE1 inhibitor, GRL-8234, for 2 months showed clear improvements in memory tests in 5xFAD AD mice (Devi et al, 2015). A six-month treatment regimen of Tg-2576 mice with another BACE1 inhibitor, TAK70, also showed decreased cerebral Aβ deposition by approximately 60% and ameliorated memory deficits (Fukumoto et al, 2010).…”
Section: Inhibiting Bace1 To Benefit Synaptic Functionmentioning
confidence: 99%